(untitled) (Research, Society and Development, 2021)
Obstructive sleep apnea (OSA) is a global disease that is associated with metabolic syndrome, especially obesity. Intermittent hypoxemia, resulting from OSA, that can lead to an increase in insulin resistance and a change in lipid metabolism, which may precipitate hepatic steatosis, characterized by the accumulation of lipids within the hepatocytes, considered a probable main cause of morbidity and mortality in liver disease. Thus, this retrospective study sought to assess a possible relationship between OSA and hepatic steatosis in obese patients in the preoperative period for bariatric surgery. From the data collection of 1,416 medical records of patients undergoing preoperative evaluation, data from ultrasound examination (US) and polysomnography (PSG) were obtained, resulting in a sample of 87 individuals. Of this sample, 61% of the individuals were female, with an average age of 39 years old (SD 11.4) and a BMI of 39.3 (SD 4,4). Ultrasonography classified 74 individuals with hepatic steatosis (85%). The average value of the Apnea-Hypopnea Index (AHI) was 33.5 (SD 28.9) and the Oxyhemoglobin Desaturation Index (ODI) 41.4 (SD 34.1). The patients were divided into 2 groups: a group with AHI less than or equal 15 events / hour and another with AHI greater than or equal 16 events / hour. The degree of steatosis differs between groups by AHI (p <0.001) and gender (p <0.001). After adjusting several variables using multiple regression, only the male sex was a predictor of higher steatosis degree. In conclusion there is a higher prevalence of hepatic steatosis among patients with OSA, and the main factors associated with steatosis were the AHI and male sex, but after regression only female sex would be the steatosis protection predictor in the study group.